Kerjasama Pengembangan Teknologi Ramah Lingkungan Pembuatan Gerabah di Indonesia dan Vietnam - Hamdiani, Saprini; Kamali, Siti Raudhatul; Safitri, Najma Nur; Risiyaningsih, Risa; Hidayatullah, Riski; Azzauri, Supyan; Hadisaputra, Saprizal; Arisanti, Ivon; Ha, Nguyen Thi The; Shofiana, Fitria; Utari, Dinda Listi; Fajrina, Cendana Sila; Maulana, Fery Andrian; Gifari, M. Arya; Puspita, Nova Maya Dela; Diwi, Imelda Ratna (Jurnal Pengabdian Inovasi Masyarakat Indonesia, 2025)
This community service program aimed to develop environmentally friendly pottery technology through collaboration between Universitas Mataram, Indonesia, and Dong Thap Community College, Vietnam. The activities were conducted in Penujak and Banyumulek Villages, Lombok, focusing on the application of composite technology using combustion ash waste and the utilization of natural dyes. The methods included socialization, focus group discussions (FGDs), and hands-on practice with local artisans. The results indicated a significant increase in participants’ knowledge regarding composite technology concepts, alternative material utilization, and combustion ash processing techniques, with an average improvement ranging from 45% to 70%. Furthermore, the practical application of natural dyes, such as sappan wood, tegeran, jolawe, indigosfera, meranti wood, and areca nut, was successfully demonstrated in pottery products. A satisfaction survey revealed that most participants were satisfied to highly satisfied with the training and were motivated to continue developing composite pottery with eco-friendly dyes. Overall, the program effectively enhanced artisans’ knowledge, skills, and motivation, while supporting the diversification of pottery products toward more innovative and globally market-oriented outcomes.